2009
DOI: 10.2223/jped.1889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term multidisciplinary inpatient therapy on body composition of severely obese adolescents

Abstract: Objective: To describe the effects of long-term multidisciplinary inpatient therapy on body composition of severely obese adolescents. Methods:A total of 728 extremely obese adolescents, including 249 boys (aged 15.25±1.56 years) and 479 girls (aged 15.34±1.59 years) received multidisciplinary therapy during a period of 3 to 9 months. The therapy consisted of reduced energy intake, dietetic education, physical exercises and psychological therapy. Body composition was assessed by bioelectrical impedance analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
0
23
0
5
Order By: Relevance
“…Earlier studies using very low calorie diets and moderate vigorous physical activity resulted in loss of LM in adults and children . Subsequent intensive inpatient studies demonstrated maintenance of LM . In this study, which used a moderate calorie restriction, LM was preserved in boys and that although the absolute LM decreases in girls, the percentage of weight that is LM continues to increase.…”
Section: Discussionmentioning
confidence: 59%
“…Earlier studies using very low calorie diets and moderate vigorous physical activity resulted in loss of LM in adults and children . Subsequent intensive inpatient studies demonstrated maintenance of LM . In this study, which used a moderate calorie restriction, LM was preserved in boys and that although the absolute LM decreases in girls, the percentage of weight that is LM continues to increase.…”
Section: Discussionmentioning
confidence: 59%
“…However, over 25% of the excess weight in obese adolescents is attributed to elevations in FFM (14) . Therefore, if the common, yet conflicting, goals of retaining or increasing FFM while subsequently maximizing weight loss (15,16) are to be realized, weight management strategies may need to emphasize one goal over the other.…”
Section: Introductionmentioning
confidence: 99%
“…The most important effects of the multidisciplinary treatment on the population investigated include improvements in the anthropometric parameters, such as the reduction in Total Body Mass (TBM) 5 36 found a significant reduction in body weight, BMI, and body fat after a nine-month intervention.…”
Section: Discussionmentioning
confidence: 99%